Description of plant communities on Half Moon Island, Antarctica - Schmitz, Daniela; Putzke, Jair; Pereira de Albuquerque, Margéli; Schünemann, Adriano Luis; Costa Beber Vieira, Frederico; de Carvalho Victoria, Filipe de Carvalho Victoria; Batista Pereira, Antônio (Polar Research, 2018)
During February–March of the austral summers of 2013/14 and 2014/2015, fieldwork was performed on Half Moon Island, South Shetland Archipelago, Antarctica, to evaluate the distribution and abundance of mosses and lichens, as well as to describe and map the plant communities there. The quadrat (20 × 20 cm) sampling method was employed in a phytosociological study that aimed to describe these communities. The area was mapped using an Astech Promark II® DGPS, yielding sub-metric precision after post-processing with software. The number of species totalled 38 bryophytes, 59 lichens, only one flowering plant (Deschampsia antarctica Desv.), and two macroscopic terrestrial algae. Five types of plant communities were identified on the island, as follows: (1) fruticose lichen and moss cushion, (2) moss carpet, (3) muscicolous lichen, (4) crustose lichen and (5) moss turf.
Keywords: Antarktis; botanikk; bryozoa; flora; fytososiologi; lav; moser; planter; økologi

Patterns of fungal–algal symbiont association in Usnea aurantiaco-atra reveal the succession of lichen–moss communities in Fildes Peninsula, Antarctica - Cao, Shunan; Peng, Fang; Zheng, Hongyuan; Liu, Chuanpeng; Zhou, Qiming (Polar Research, 2017)
Usnea aurantiaco-atra is the most widespread flora in Fildes Peninsula. There are two growth types of U. aurantiaco-atra: the erect form on rocks and the prostrate form associated with mosses. Phylogenetic analysis showed that individuals of the two growth forms share genotypes. Moreover, haploid disequilibrium testing indicated no significant genetic difference for the two growth forms when fungal and algal internal transcribed spacer rDNA were treated as two alleles of one lichen individual. The two growth forms of U. aurantiaco-atra appear to reflect different stages of lichen–moss community succession. A mode is proposed for demonstrating the occurrence of this succession.
Keywords: Antarktis; botanikk; flora; fylogenetikk; lav; moser; planter

Antarktis - kort fortalt - Balto, Ann Kristin; Hallanger, Ingeborg Gammelsæter; Jenssen, Elin Vinje (Norsk polarinstitutt, 2015)
Keywords: Antarktis; biologi; fauna; flora; historie; klima; miljø; natureklima; naturhistorie

Mapping lichen distribution on the Antarctic Peninsula using remote sensing, lichen spectra and photographic documentation by citizen scientists - Casanovas, Paula; Black, Martin; Fretwell, Peter; Convey, Peter (Polar Research, 2015)
On the Antarctic Peninsula, lichens are the most diverse botanical component of the terrestrial ecosystem. However, detailed information on the distribution of lichens on the Antarctic Peninsula region is scarce, and the data available exhibit significant heterogeneity in sampling frequency and effort. Satellite remote sensing, in particular the use of the Normalized Difference Vegetation Index (NDVI), has facilitated determination of vegetation richness and cover distribution in some remote and otherwise inaccessible environments. However, it is known that using NDVI for the detection of vegetation can overlook the presence of lichens even if their land cover is extensive. We tested the use of known spectra of lichens in a matched filtering technique for the detection and mapping of lichen-covered land from remote sensing imagery on the Antarctic Peninsula, using data on lichen presence collected by citizen scientists and other non-specialists as ground truthing. Our results confirm that the use of this approach allows for the detection of lichen flora on the Antarctic Peninsula, showing an improvement over the use of NDVI alone for the mapping of flora in this area. Keywords: Antarctica; NDVI; matched filtering; Landsat; remote sensing.
Keywords: Antarktis; botanikk; flora; lav; satellitt bilder; økosystemer

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer

Assessing the importance of human activities for the establishment of the invasive Poa annua in Antarctica - Molina-Montenegro, Marco A; Carrasco-Urra, Fernando; Acuña-Rodriguez, Ian; Oses, Rómulo; Torres-Diaz, Cristian; Chwedorzewska, Katarzyna J (Polar Research, 2014)
Because of its harsh environmental conditions and remoteness, Antarctica is often considered to be at low risk of plant invasion. However, an increasing number of reports have shown the presence and spread of non-native plants in Antarctica; it is therefore important to study which factors control the invasion process in this ecosystem. Here, we assessed the role of different human activities on the presence and abundance of the invasive Poa annua. In addition, we performed a reciprocal transplant experiment in the field, and a manipulative experiment of germination with P. annua and the natives Colobanthus quitensis and Deschampsia antarctica, in order to unravel the effects of physical soil disturbance on the establishment and survival of P. annua. We found a positive correlation between abundance of P. annua and level of soil disturbance, and that survival of P. annua was 33% higher in sites with disturbed soil than non-disturbed. Finally, we found that disturbance conditions increased germination for P. annua, whereas for native species germination in experimentally disturbed soil was either unchanged or reduced compared to undisturbed soil. Our results indicate that human activities that modify abiotic soil characteristics could play an important role in the abundance of this invasive species. If the current patterns of human activities are maintained in Antarctica, the establishment success and spread of P. annua could increase, negatively affecting native flora. Keywords: Alien species; Colobanthus quitensis; Deschampsia antarctica; human disturbance; Poa annua; tourists.
Keywords: Antarktis; biodiversitet; flora; menneskelig påvirkning; planter; turisme; økosystemer

Colonization and demographic structure of Deschampsia antarctica and Colobanthus quitensis along an altitudinal gradient on Livingston Island, South Shetland Islands, Antarctica - Vera, María Luisa (Polar Research, 2011)
The colonization capacity and demographic structure of populations of Deschampsia antarctica and Colobanthus quitensis were studied in different microhabitats between 10 and 147 m a.s.l. on Livingston Island, South Shetland Islands, near the Spanish Antarctic base Juan Carlos I, in February 2002. At the highest site (147 m a.s.l.), mean temperatures were about 1 ºC lower than at sea level. Both species are less common in inland areas and at the highest altitudes only occur at restricted sites that are frequently snow-free in the early austral summer. The diameters of the largest plants (C. quitensis cushions 7-8 cm ; D. antarctica tufts 10-11 cm) in the populations growing at the highest altitudes (110 and 147 m a.s.l.) suggest that these populations were established about 24-28 years ago. The largest diameter plants (Deschampsia 20 cm; Colobanthus 18 cm) were found at the lowest altitudes on deep soil. The presence of numerous seedlings and young individuals on the periphery of populations established several years ago or at recently colonized sites suggests an active process of expansion. There were more emerged seedlings of C. quitensis than of D. antarctica, but the density of established individuals was higher for D. antarctica, suggesting these species have different demographic strategies. Keywords: Antarctic vascular plants; altitude and habitat effect; colonization; population structure.
Keywords: Antarktis; biologi; flora; planter